Aortic–Radial Pulse Wave Velocity Ratio in End-stage Renal Disease Patients: Association with Age, Body Tissue Hydration Status, Renal Failure Etiology and Five Years of Hemodialysis - Bia, Daniel; Valtuille, Rodolfo; Galli, Cintia; Wray, Sandra; Armentano, Ricardo; Zócalo, Yanina; Cabrera-Fischer, Edmundo (High blood pressure & cardiovascular prevention, 2017)
Introduction The etiology of the end-stage renal disease (ESRD) and the hydration status may be involved in the arterial stiffening process observed in hemodialyzed patients. The ratio between carotid-femoral and carotid-radial pulse wave velocity (PWV ratio) was recently proposed to characterize the patient-specific stiffening process. Aims: to analyze: (1) the PWV-ratio in healthy and hemodialyzed subjects, analyzing potential changes associated to etiologies of the ESRD, (2) the PWV-ratio and hydration status using multiple-frequency bioimpedance and, (3) the effects of hemodialysis on PWV-ratio in a 5-year follow-up. Methods PWV-ratio was evaluated in 151 patients differentiated by the pathology determining their ESRD. Total body fluid (TBF), intra and extra cellular fluid (ICF, ECF) were measured in 65 of these patients using bioelectrical-impedance. The association between arterial, hemodynamic or fluid parameters was analyzed. PWV-ratio was evaluated in a group of patients (n = 25) 5 years later (follow-up study). Results PWV-ratio increased in the ESRD cohort with respect to the control group (1.03 ± 0.23 vs. 1.31 ± 0.37; p < 0.001). PWV-ratio in the diabetic nephropathy group was higher than in all other etiological groups (1.61 ± 0.33; p < 0.05). PWV-ratio was associated with TBF (r = −0.238; p < 0.05), ICF (r = −0.323; p < 0.01), ECF/ICF (r = 0.400; p < 0.001) and ECF/TBF (r = 0.403; p < 0.001). PWV-ratio calculated in ESRD patients in 2007 increased 5 years later (1.14 ± 0.32 vs. 1.43 ± 0.44; p < 0.005). Conclusions PWV-ratio increased the most in patients with diabetic nephropathy. PWV ratio was significantly associated with age and body hydration status, but not with the blood pressure. PWV-ratio could be considered a blood pressure-independent parameter, associated with the age and hydration status of the patient.